Influence of dates of sowing and moisture regimes in pigeonpea on population dynamics of Fusarium udum at different soil strata - and VISHWA DHAR, R.G. CHAUDHARY, KUMUD KUMAR* (Indian Phytopathology, 2002)
Studies in pigeonpea conducted during two consecutive years revealed that early sown crop (1st July) exhibited higher Fusarium udum inoculum in wilt sick plot which gtradually decreased in subsequent dates with least population in 16th September sown crop. This could be attributed to more root biomass and increased plant age of early sown crop. Irrigated fields showed significantly increased population over rainfed throughout the two years of cropping. Even the effect of sowing dates on pathogen population dynamics was more pronounced under irrigated conditions than that under rainfed. Top 15 em stratum invariably had highest population followed by middle 15-30 cm and lower 30- 45 cm stratum. Increase in population in ’upper stratum was higher during the pigeonpea cropping periods while in middlestratum it was higher during 2nd cropping. Population increase in lower stratum was steady and linear. Pigeonpea cropping in the same field increased F. udum population from 1.89 thousand cfu/g soil to 3.99 thousand at the harvest of Ist crop and to 10.13thousand cfu/g soil at the harvest of 2nd crop. However, the inoculum level of even 0.66 thousand cfu/g soil could cause 71.4% wilting in susceptible variety Bahar in the established sick field.